Migrant Academics' Narratives of Precarity and Resilience in Europe - Burlyuk, Olga; Rahbari, Ladan (Open Book Publishers, 2023)
This volume consists of narratives of migrant academics from the Global South within academia in the Global North. The autobiographic and autoethnographic contributions to this collection aim to decolonise the discourse around academic mobility by highlighting experiences of precarity, resilience, care and solidarity in the academic margins. The authors use precarity to analyse the state of affairs in the academy, from hiring practices to 'culturally' accepted division of labour, systematic forms of discrimination, racialisation, and gendered hierarchies, etc. Building on precarity as a critical concept for challenging social exclusion or forming political collectives, the authors move away from conventional academic styles, instead adopting autobiography and autoethnography as methods of intersectional scholarly analysis. This approach creatively challenges the divisions between the system and the individual, the mind and the soul, the objective and the subjective, as well as science, theory, and art. This volume will be of interest not only to scholars within the field of migration studies, but also to instructors and students of sociology, postcolonial studies, gender and race studies, and critical border studies. The volume's interdisciplinary approach also seeks to address university diversity officers, managers, key decision-makers, and other readers directly or indirectly involved in contemporary academia. The format and style of its contributions are wide-ranging (including poetry and creative prose), thus making it accessible and readable for a general audience.